Le métier de tuilier à Paris au xve siècle : approche sociale et organisation du travail dans la juridiction de Saint-Germain-des-Prés - Stéfan Gouzouguec (Archéologie Médiévale, 2006)
Through analysis of the seigneurial accounts and particularly the notarial deeds, the economic and social aspects of the ceramic building materials trade are well known for a number of regions such as Burgundy, Provence, Normandy and the Toulouse environs. Luckily, the lack of such sources for Paris can be partly compensated by the analysis of legal sources from the Saint-Germain-des-Prés abbey, enabling us to analyse the tileries established on the left bank. Far from anecdotic, the seigneurial justice registers throw light on certain aspects sometimes hidden in other sources. They enable us to apprehend work organisation in detail, as well as the social relationships between the different categories of collaborators in the trade (tilery owners, tilers, employees, suppliers), and to single out certain Parisian particularities. As well as the early independence of the activity as regards to the different authorities, doubtlessly due to the importance of the Parisian building market, the legal conditions of the exercise show a trade for which regulations are both less strict than is the case for other trades, and less strict than those in vigour in other regions.